Rozciąganie Silami Skupionymi Tarczy Nieograniczonej z Otworem Kołowym / Rozciąganie Silami Skupionymi Tarczy Nieograniczonej z Ośrodkiem Sztywnym Zarysu Kołowego - Szelągowski, F. (Engineering Transactions, 1956)
The stresses Ro, R, and 09 at any point of an infinite plate having a circular hole of radius R and subjected to tension by two concentrated forces P acting at the distances a from the centre of the hole are determined by Eqs. (11), (12) and (13), respectively. The equations under consideration are valid only for values of a contained in the interval R<a< ∞. The value of the stress θθ for r = R and θ = 90° in the infinite plate is, in the case of the forces P acting at the periphery of the hole, almost 4 times as high as the corresponding value in the case of a plate without a hole. / The stresses Rθ, R, and θθ at any point of an infinite plate having a rigid circular inclusion of radius R and subjected to tension by two concentrated forces P acting at the distances a from the centre of the inclusion are expressed by Eqs. (11), (12) and (13), respectively. The value of the stress R, for r = R and θ = 0 of the infinite plate is, for relatively small values of d/R, almost 1,6 times as high as the corresponding value in the case of a homogeneous plate (i. e. without inclusion).